Strategi Pembelajaran Aqidah Akhlak dalam Proses Belajar Siswa Kelas VII MTs Alfathimiyah Karawang - Lula Nur’aeni; Tajudin Nur; Yayat Herdiana (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The teaching and learning process is a very useful subject, because it is this process that ensures the learning objectives are achieved or not achieved. Madrasah Tsanawiyah as a form of Islamic learning institution which is believed to have a position and direct involvement in the process of character building for students. Aqidah Morals is a good module that is taught by each level of the madrasa, this module is expected to shape the behavior and attitudes of students for the better. And this educational strategy guidance makes achieving success or success in achieving goals. There is also a formulation of the research problem, namely 'How is the application of the aqidah akhlaq learning strategy that is usually carried out by class VII students of Mts Alfathimiyah Karawang?'. There is also the purpose of this research to find out the learning strategies of aqidah akhlaq which are usually carried out by class VII students of Mts Alfathimiyah Karawang. This research uses a qualitative method by using primary information (Teachers and Students at Mts Alfathimiyah Karawang) and secondary information (books and the Internet). Sourced on the results of research on Aqidah Morals learning strategies at MTs Alfathimiyah Karawang. There is a conclusion that expository learning strategies for aqidah akhlaq subjects in class VIIA MTs Alfathimiyah Karawang are more efficient and efficient than inquiry learning strategies and cooperative learning strategies.